Researching Architectural Salvage through Experiential Education - Clouse, Carey (ARCC Conference Repository, 2014)
In the streets of post-Katrina New Orleans, it was trash heaps, rather than signage, that offered the promise of a homeowner's return. Street-side mountains of soggy sheetrock, worn-out flooring and old windows provided a visual testament of rebuilding efforts inside; these piles of architectural debris framing gutted houses on almost every block. Such material waste regularly accompanies standard construction practices, where the yardstick of progress measures the number of dumpsters filled, and transformation implies resource depletion. This perverse line of thinking was called into question by one team of architecture students at Tulane University, who in the midst of the post-Katrina rebuilding of New Orleans, sought to illuminate demolition excesses and the untapped potential inherent to such processes. Their efforts to identify the type and scope of this material waste led to extensive field-based data collection, material cataloging and resource mapping. Once they had completed this exhaustive product index, the design team produced an alternative concept of one such trash heap, demonstrating the productive capacity of design thinking and the value of direct action in the face of wasteful rebuilding practices.